А new Gal/GalNAc-specific lectin from the mussel Mytilus trossulus: Structure, tissue specificity, antimicrobial and antifungal activity. (March 2016) - Chikalovets, Irina V.; Kovalchuk, Svetlana N.; Litovchenko, Alina P.; Molchanova, Valentina I.; Pivkin, Mikhail V.; Chernikov, Oleg V.
Abstract: In the present study, a new Gal/GalNAc specific lectin from the mussel Mytilus trossulus (designated as MTL) was identified, and its expression levels, both in tissues and toward pathogen stimulation, were then characterized. The MTL primary structure was determined via cDNA sequencing. Deduced sequence of 150 amino acid residues showed 89% similarity to lectins from the mussels Crenomytilus grayanus and Mytilus galloprovincialis that were the first members of a new family of zoolectins. The results indicated that the MTL might be involved in immune response toward pathogen infection, and it might perform different recognition specificity toward bacteria or fungi. Highlights: The amino acid sequence a lectin from the mussel Mytilus trossulus was determined. The lectin is a member of a novel lectin family. It was shown that the lectin is a β/α-protein. The lectin exhibits the antibacterial and antifungal activity.